Efficacy and safety of azathioprine, mycophenolate mofetil, and reduced dose of rituximab in neuromyelitis optica spectrum disorder. (27th April 2022) - Huang, Wenjuan; Wang, Liang; Xia, Junhui; Li, Wenyu; Wang, Min; Yu, Jian; Li, Qinying; Wang, Bei; Pan, Juyuan; Du, Lei; Ma, Jianhua; Tan, Hongmei; et al.
Abstract: Background and purpose: Data regarding the efficacy and safety of currently widely available preventive therapies in neuromyelitis optica spectrum disorder (NMOSD) are needed. We compared the efficacy and safety of azathioprine (AZA), mycophenolate mofetil (MMF), and reduced dose of rituximab (RTX) in NMOSD based on a large multicenter retrospective cohort. Methods: Patients with aquaporin 4 (AQP4) antibody‐positive NMOSD with AZA ( n  = 167), MMF ( n  = 131), or RTX ( n  = 55) as initial preventive treatment were included. The main outcome was the occurrence of relapse after the initiation of immunotherapy. Secondary outcomes were annual relapse rate, disability accumulation, drug persistence, and adverse events. Results: The median follow‐up time of the 353 patients was 30.3 months. The regimen of RTX was 100 mg on Day 1 and 500 mg on Day 2, followed by 500 mg every 6 months. The proportions of patients with concomitant steroid therapy at baseline were 96.4%, 95.4%, and 76.4% in the AZA, MMF, and RTX groups. Risk of relapse was significantly reduced in patients treated with RTX compared with those treated with AZA (hazard ratio [HR] = 4.40, 95% confidence interval [CI] = 1.41–13.80, p  = 0.011) or MMF (HR = 5.20, 95% CI = 1.60–16.86, p  = 0.006) after adjusting for potential confounding variables. Drug discontinuations were less likely on RTX than AZA (HR = 2.22, 95% CI = 1.34–3.66, p  = 0.002). RTX exhibited lower incidence of adverse events (32.7%) than AZA (62.3%, p  < 0.001). Conclusions: We provide Class III evidence that reduced dose of RTX is superior to AZA and MMF as initial treatment to reduce the risk of relapse and is better tolerated than AZA in Chinese patients with AQP4 antibody‐positive NMOSD. Abstract : Reduced dose of rituximab (RTX; 100 mg on Day 1 and 500 mg on Day 2 followed by 500 mg every 6 months) is superior to azathioprine (AZA) and mycophenolate mofetil as initial treatment to reduce the risk of relapse in patients with aquaporin 4 antibody‐positive neuromyelitis optica spectrum disorder. Drug discontinuations were less likely on RTX than AZA, and RTX is better tolerated than AZA.